Ethnoveterinary practice of medicinal plants in Chhatradev Rural Municipality, Arghakhanchi District of Western Nepal - Alok Dhakal; Sushank Khanal; Meena Pandey (Smujo International, 2021)
Abstract. Dhakal A, Khanal S, Pandey M. 2021. Ethnoveterinary practice of medicinal plants in Chhatradev Rural Municipality, Arghakhanchi District of Western Nepal. Nusantara Bioscience 13: 29-40. The use of medicinal plants is a traditional system in treating domestic animals in Nepal. This study was done to investigate and document knowledge about using different plants with medicinal value to cure different animal ailments in Chhatradev Rural Municipality, Arghakhanchi district of western Nepal. A total of 100 elderly people rearing domestic animals and having traditional knowledge of ethnoveterinary plants were selected for interview. A semi-structured questionnaire was employed, and interviews were conducted for addressing detailed ethnoveterinary information. The uses of 103 plant species belonging to 56 families were documented for the treatment of 21 animal ailments. Fabaceae was found to be a dominant family with 10 plant species followed by Poaceae (8 species). The most commonly used plant parts were leaf, seed, and fruit. Herbs were dominant with 44 plant species followed by trees (32 species), shrubs (14 species), and climbers (13 species). The wide application of the medicinal plants as the form of paste formulation was observed for 41 plant species, while 25 plant species were used as powder formulation followed by Juice (21 species), raw (20 species), decoction (19 species), infusion (5 species), and roasted formulation (3 species). Oral route was the most common route followed by dermal and ocular. It was found that the informant consensus factor (ICF) values varied from 0.858 to 0.96. A high informant consensus factor was found for ailment of reproductive category (0.96) followed by respiratory (0.957), gastrointestinal (0.949) while the least was in urinary problem category (0.858). The highest citation frequency was found for Trachyspermum ammi (L.) Sprague (247) followed by Myristica fragrans Houtt. (111), Sesamum indicum L. (109), Saccharum officinarum L. (107) and Zea mays L. (97). The wide use and rich knowledge of ethnoveterinary practice were found in the study area. This study might be handy to discover useful ethnopharmaceutical agents applicable in the livestock industry. Conservation programs should be done from the government level and study on the use of medicinal plants for treating animal diseases is recommended.